(untitled) (London Journal of Medical and Health Research, 2025)
Background: Traffic accident-related traumas are the leading cause of mortality among adolescents and young adults aged 15 to 29 years. Furthermore, they represent a considerable financial burden on public finances, with estimated costs of approximately 3% of the annual GDP, impacting sectors such as healthcare, infrastructure, and productivity. Accidents commonly result in polytrauma, and various criteria have been established to assess injury severity in frontal vehicle collisions. Therefore, this study aims to conduct a literature review to investigate the main patterns of injuries observed in frontal vehicle collisions over the past five years. Methodology: This is a literature review conducted between November and December 2024, utilizing the MEDLINE database. The search employed the keyword "frontal car crashes" and was restricted to studies published within the last five years. The initial search yielded 102 articles, and after screening, using inclusion criteria such as reporting injuries from frontal vehicle collisions with human models or real-life cases, other literature reviews were excluded. A total of 8 articles were selected.